PENGARUH PEMBERIAN AIR REBUSAN BIJI ALPUKAT (Persea americana Mill) TERHADAP PERTUMBUHAN JAMUR Candida albicans SECARA IN VITRO - Amir, Nayla Nabilla Tahta Avwina; Winarsih, Sri; Rahardjo, Bambang (-)
The most common cause of patalogis leucorrhoea is infection, one of which is Vulvovaginal Candidiasis (VVC) caused by fungus, while 80% -90% is caused by Candida albicans. Approximately 90% of young women in Indonesia have the potential to experience vaginal discharge because Indonesia is a tropical climate. Alternative treatment for antifungal drugs is needed through the exploration of natural material sources that have the potential as antifungals to deal with this infection safely and easily. The design used in this study was experimental research by in vitro using the dilution method of the tube. Treatment concentrations are 45%; 40%; 35%; 30%; 25%; 20%, 15% and 0% with Candida albicans 104 CFU / ml samples from the microbiology lab of the medical faculty Brawijaya University and repeated 3 times. The result showed that at all concentrations, growth was still obtained in agar media so that it could be denied that the boiled water of avocado seeds had no effect on the growth of Candida albicans fungal colonies in vitro because there were still fungal colonies on the plates.